2014
DOI: 10.1136/bmjopen-2013-004303
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients develop severe pressure ulcers? A retrospective case study

Abstract: ObjectivesThis study focuses on the ways in which the organisational context can influence the development of severe pressure ulcers. Severe pressure ulcers are important indicators of failures in the organisation and delivery of treatment and care. We have a good understanding of patients’ risk factors, but a poor understanding of the role played by the organisational context in their development.SettingThe study was undertaken in six sites in Yorkshire, England. The settings were sampled in order to maximise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
1
18
2
2
Order By: Relevance
“…It appears that there has been little patient involvement in the process with less than half of the patients who developed a severe PU being interviewed (table 1). Previous research [10] has identified that organisational factors are often key in identifying the root cause; however this was not reflected in this study.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…It appears that there has been little patient involvement in the process with less than half of the patients who developed a severe PU being interviewed (table 1). Previous research [10] has identified that organisational factors are often key in identifying the root cause; however this was not reflected in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have identified nd to increased risk of PUs [10], however this study did not identify why staff overlooked the patients nutritional needs or the barriers to communication between medical and nursing staff regarding nutrition.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Hasta ve hasta yakınlarının yetersiz dinlemek, yetersiz muayene, klinisyenlerin yüksek riskli kişilerde bası yarası bulgularını tanımada yetersizlik, servisler arasında kordinasyonun etkin olmaması nedenleri ile şiddetli bası yaralarının geliştiği görülmüştür (23). Evde sağlık hizmeti, yatağa bağımlı hastaların düzenli muayenesinin yapılması, gereklilik durumunda diğer servislerle koordinasyonun sağlanması açısından önem taşımaktadır.…”
Section: Materyal Metodunclassified
“…In a further SCR, Wood (2014) (Pinkney et al 2014). In a small number of localities there were policies and procedures at the time stating that some (severe) or all pressure ulcers should be reported as a safeguarding alert.…”
Section: Family Contextsmentioning
confidence: 99%